Palmitoleic acid protects microglia from palmitate-induced neurotoxicity in vitro. - Qingting Yu; Yanzhuo Yang; Ting Xu; Yinsheng Cai; Zuisu Yang; Falei Yuan (PLoS ONE, 2024)
Although palmitoleic acid (POA) is a lipokine with beneficial effects on obesity and is produced as a byproduct from the manufacture of prescription omega-3 fatty acids, its role in nervous system inflammation is still unknown. This study aims to examine the mechanisms and protective effects of POA against palmitic acid (PA)-induced microglial death. PA-induced microglial death was used as a model for POA intervention. Various inhibitors were employed to suppress potential routes of PA entry into the cell. Immunofluorescence staining and Western blotting were conducted to elucidate the protective pathways involved. The results suggest POA has the potential to eliminate PA-induced lactate dehydrogenase (LDH) release, which decreases the overall number of propidium iodide (PI)-positive cells compared with control. Moreover, POA has the potential to significantly increase lipid droplets (LDs) in the cytoplasm, without causing any lysosomal damage. POA inhibited both canonical and non-canonical gasdermin D (GSDMD)-mediated pyroptosis and gasdermin E (GSDME)-mediated pyroptosis, which PA typically induces. Additionally, POA inhibited the endoplasmic reticulum (ER) stress and apoptosis-related proteins induced by PA. Based on the findings, POA can exert a protective effect on microglial death induced by PA via pathways related to pyroptosis, apoptosis, ER stress, and LDs.